Challenges and opportunities for disseminating archaeology in Portugal: different scenarios, different problems - Sousa, Ana Catarina (2016)
From Valletta to Faro, much has changed in Portuguese archaeology: legislation, archaeologists, heritage administration and communication with society. Several archaeological stakeholders recognise that dissemination is still one of the major gaps in post-Valletta Portuguese archaeology. This article will separately analyse the main problems and opportunities in disseminating archaeological knowledge in Portugal, using case studies and crossing data with some personal views. For different actors and contexts there are different challenges and opportunities many lost, others rediscovered. The following scenarios will be retrospectively analysed: 1. Urban archaeology (Lisbon), 2. Rescue archaeology in major projects (EDIA – Alqueva Development and Infrastructure Company), 3. Archaeology in the municipalities (Mafra), 4. Archaeology in universities and research centres (UNIARQ – Centre of Archaeology at the University of Lisbon), 5. Archaeology by the cultural heritage authorities (IPA – Instituto Português de Arqueologia, IPPAR – Instituto Português do Património Arqueológico e Arquitectónico), IGESPAR – Instituto de Gestão do Património Arquitectónico, DGPC – Direcção Geral do Património), 6. Community and associative archaeology. This review will cover the period between 1997 and 2014, beginning with the date of ratification of the Valletta Convention in Portugal.